Sosialisasi Deteksi Dini Penyakit Tidak Menular dan Pemeriksaan Kesehatan dengan Metode POCT - Wirdullutfi; Baiq Isti HIjriani; Heru Setiawan; Eni Suyantri; Marosa Robi’atul Adawiyah (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service program aims to enhance participants' knowledge, awareness, and independence in the early detection of non-communicable diseases (NCDs) through blood pressure, blood glucose, and uric acid screening, as an effort to control NCD cases in line with the 2030 Sustainable Development Goals (SDGs) for global well-being. The methods implemented included socialization and health screenings for 55 participants (average age 41 years; range 26-56 years; 67% male, 33% female), with 50 participants screened for blood glucose and uric acid (74% male, 26% female). Screening results showed: normal blood pressure in 45 people (81.9%), prehypertension in 8 people (14.5%), stage 1 hypertension in 2 people (3.6%); normal blood glucose in 44 people (88%), prediabetes in 5 people (10%), diabetes in 1 person (2%); and normal uric acid levels in 47 people (94%), hyperuricemia in 3 people (6%). All participants understood the importance of early NCD detection and committed to creating a healthier and more productive community.